COMPARATIVE ANALYSIS OF THE FUNCTIONS OF PROBATION OFFICERS IN CONDITIONAL SENTENCES UNDER THE FORMER CRIMINAL CODE AND SUPERVISION AND COMMUNITY SERVICE SENTENCES UNDER THE NATIONAL CRIMINAL CODE - Fahrurozi Saputra; Erlina Bachri (Universitas Nusa Cendana, 2026)
The development of sentencing policy in Indonesia reflects a paradigm shift from imprisonment-oriented punishment toward supervision-based and social reintegration–oriented sanctions. This shift is evident in the comparison between conditional sentences under the former Indonesian Criminal Code (KUHP) and supervision and community service sentences under the National Criminal Code, which has significant implications for the functions of Community Counselors. This study aims to analyze and compare the functions of Community Counselors in the implementation of conditional sentences under the former KUHP with their roles in supervision and community service sentences under the National Criminal Code, with a case study conducted at the Class I Probation Office of Bandar Lampung. The research employs a normative juridical method with statutory and conceptual approaches, supported by empirical data obtained through interviews and document analysis. The findings indicate that under the former KUHP, the role of Community Counselors was largely administrative, focusing on monitoring compliance with sentencing conditions with limited scope for social guidance. In contrast, the National Criminal Code expands the role of Community Counselors to include guidance, supervision, mentoring, and evaluation in the implementation of supervision and community service sentences. This expanded role positions Community Counselors as key actors in the success of non-custodial sanctions aimed at rehabilitation and social reintegration. The study concludes that the sentencing reform under the National Criminal Code necessitates the strengthening of institutional capacity and human resources of Community Counselors to ensure the effective realization of humane and restorative sentencing objectives. Keywords: Community Counselors; Conditional Sentences; Supervision Sentences; Community Service Sentences; Former Criminal Code; National Criminal Code